2007
DOI: 10.1158/1078-0432.ccr-06-1109
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Negative Paradox: Primary Tumor Chemosensitivity of Breast Cancer Subtypes

Abstract: Purpose: Gene expression analysis identifies several breast cancer subtypes. We examined the relationship of neoadjuvant chemotherapy response to outcome among these breast cancer subtypes. Experimental Design: We used immunohistochemical profiles [human epidermal growth factor receptor 2^positive (HER2+)/hormone receptor^negative for HER2+/estrogen receptorn egative (ERÀ), hormone receptor and HER2À for basal-like, hormone receptor^positive for luminal] to subtype a prospectively maintained data set of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

74
1,439
7
38

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,815 publications
(1,577 citation statements)
references
References 23 publications
74
1,439
7
38
Order By: Relevance
“…17,18 Immunohistochemical marker panels that have been proposed to define basal-like breast cancers include: (1) lack of ER, PR, and HER2 expression ('triple-negative' immunophenotype); (2) expression of one or more high-molecular-weight/ basal cytokeratins (CK5/6, CK14, and CK17); (3) lack of expression of ER and HER2 in conjunction with expression of CK5/6 and/or epidermal growth factor receptor (EGFR); 17 and (4) lack of expression of ER, PR, and HER2 in conjunction with expression of CK5/6 and/or EGFR. 19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 Immunohistochemical marker panels that have been proposed to define basal-like breast cancers include: (1) lack of ER, PR, and HER2 expression ('triple-negative' immunophenotype); (2) expression of one or more high-molecular-weight/ basal cytokeratins (CK5/6, CK14, and CK17); (3) lack of expression of ER and HER2 in conjunction with expression of CK5/6 and/or epidermal growth factor receptor (EGFR); 17 and (4) lack of expression of ER, PR, and HER2 in conjunction with expression of CK5/6 and/or EGFR. 19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…24,28,59,[61][62][63] This aggressiveness is best exemplified by the fact that the peak risk of recurrence is between the first and third years and the majority of deaths occur in the first 5 years following therapy. 59,61 Patients with triple-negative cancers, 59,63 similar to those with basal-like cancers, 42 have a significantly shorter survival following the first metastatic event when compared with those with non-basal-like/non-triple-negative controls.…”
Section: S Badve Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Most women with triple negative tumors will respond to chemotherapy to some extent, but many will experience recurrence or metastatic disease. 122 Responses in this subset are heterogeneous, and further stratification and development of new targeted therapies are needed.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%